The Role and Significance of Education in the Development of Uzbek Applied Arts and Crafts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Applied arts and crafts have always beyen a part of human life in the development of mankind. This article discusses in detail the role and importance of education in the development of applied arts and crafts, its role in the discovery of young talents who are just beginning to enter the field. There are also the author’s personal views on the problems of the education system and their solutions for the development of this area.